An interactive and iterative evaluation approach for creating collaborative learning environments - Mirijamdotter, Anita; Somerville, Mary M.; Holst, Marita (Luleå tekniska universitet, Innovation och Design, 2006)
Inspired by a three-year Creative University ‘arena' initiative at Luleå University of Technology in Sweden, an international team of faculty researchers conducted an exploratory study in 2005, which aimed to investigate the efficacy of an interactive design and evaluation process for technology-enabled collaborative learning environments. This applied research approach was designed as a collaborative evaluation process for co-creation of technology-enabled, learningfocused physical and virtual ‘learning commons.' Faculty researchers from Sweden and the United States used Soft Systems Methodology tools, including the Process for Organisational Meanings (POM) model, to guide sixty-two students' participatory co-design and evaluation activities. In this paper, the POM evaluation model is explained and related to the Japanese concept Ba. Application of the models is illustrated within the context of student learning through boundary crossing information exchange and knowledge creation. As evidenced in their iterative and interactive evaluative recommendations, students' learning outcomes included development of improved capabilities for identifying socio-technical elements of distributed learning environments, suggesting that student beneficiaries can successfully reflect upon their experiences and provide valuable evaluation insights. In addition, when this evaluation is iterative, students' insights into project management, software needs, and services design can improve their technology-enabled learning experiences. Concluding comments explore the efficacy of the POM model implementation for guiding other learning-focused, user-centric initiatives, which aim to promote interdisciplinary, or boundary crossing, exchanges concurrent with advancing team-based knowledge creation proficiencies among project participants. Validerad; 2006; 20070629 (anita_g)